Integrating the Hexahelix Model and Culturally Community-Based Tourism (CCBT) in the Development of Sustainable Urban Ecotourism: A Study of Kampung Lawas Maspati in Surabaya - Muhammad Diwanul Mujahidin; Warsono W; Wisnu W; Septina Alrianingrum; Agus Suprijono; Harmanto H; Zohaib Hassan Sain (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study aims to analyze the implementation of Culturally Community-Based Tourism (CCBT), identify the roles of actors within the Hexahelix model, and explain the integration of both concepts in fostering environmental awareness practices in Kampung Lawas Maspati, Surabaya. The research employed a qualitative approach with a case study design. Data were collected through observation, in-depth interviews, and documentation, and analyzed using an interactive data analysis technique consisting of data reduction, data display, and conclusion drawing. The findings reveal that the implementation of CCBT in Kampung Lawas Maspati successfully integrates cultural preservation, community empowerment, and sustainable environmental management. The local community plays a central role in maintaining environmental cleanliness, preserving cultural heritage, developing local micro-enterprises, and strengthening the value of mutual cooperation (gotong royong) as the village’s social capital. Furthermore, the Hexahelix model, involving government, academics, business sector, media, community, and supporting partners, has strengthened multi-stakeholder collaboration in promoting sustainable ecotourism development. The integration of Hexahelix and CCBT has generated various environmental stewardship practices, including urban greening, waste bank management, productive utilization of limited spaces, and the implementation of the Kampung Madani Program. The findings also indicate that these practices are consistent with the principles of deep ecology, which view the environment as an integral part of social life rather than merely an economic resource.